Alcohol use disorders and carbonhydrate deficient transferrin (cdt) - Konuk, Numan; Kıran, Sibel; Can, Murat; Atik, Levent; Evcuman, Durmuş (Journal of Dependence, 2007)
Biological markers keep their importance in search of complementary factors helping to detect alcohol dependence and abuse as a legal matters. In this review the diagnostic validity of carbonhydrate deficient transferrin which is one of the biological markers in alcohol usage disorders were compared with other markers and studies were revised under this topic. We propose practical advices when issuing driver licence and giving back delayed licences to prevent traffic accidents which are among the most serious public health problem in our country.
Keywords: Alcohol use disorders; biological markers; carbonhydrate deficient transferin; traffic accidents